Considering dynamic parameters of damaged structure in MPA and YPS nonlinear static procedures for asymmetric buildings. (7th January 2013) - Moslemi, Mehdi; Chizari, Hossein; Moghadam, Abdolreza Sarvghad
SUMMARY The yield point spectra and modal pushover procedures have already been used in seismic design of new buildings and vulnerability evaluation of existing structures. This paper initially identifies the similarities and differences of the two procedures. Then, the modal characteristics of damaged structure are used to modify their methodologies. The applications of the procedures in estimating displacement, interstory drift index and plastic hinge rotation responses of asymmetric buildings are investigated for three 5‐story reinforced concrete moment‐resisting frame‐building models. The results show considerable improvement in estimating the responses of those asymmetric buildings. Copyright © 2013 John Wiley & Sons, Ltd.